Modification of polyethylene for oil-water separation in industrial wastewater treatment - Mashael Al-Maas (14152386) (2024)
Low-density polyethylene (LDPE) is extensively used worldwide in various applications due to its versatile features and abundant commercial availability. This study investigated, for the first time, the beneficial use of a novel chemically modified commercial-grade LDPE as a sorbent for oil-water separation in industrial wastewater treatment. Several laboratory tests were conducted in batch and continuous fixed-bed modes to evaluate the LDPE adsorbent’s capacity, performance repeatability and recyclability under relevant field conditions. These results were compared to walnut shell (WS), a widely used sorbent for removing oil from industrial wastewaters, including produced water from oil and gas operations. Untreated LDPE achieved higher total organic carbon (TOC) removals and retention capacities, ∼20 % and ∼66 mg/g, respectively, when compared to untreated WS, <5 % and <1 mg/g, respectively. Improved kinetics and adsorption behavior favorability were achieved for LDPE after chemical modification using a cationic monomer. Both the chemically treated LDPE and WS showed comparable TOC removal rates (ranging from 60 % to 80 %). However, the modified LDPE exhibited higher sorption capacities (∼61 mg/g) compared to the treated WS (8.0 mg/g). Chemical regeneration of LDPE with toluene demonstrated superior performance recovery (>90 %) when compared to physical cleaning with deionized water (<40 %). The study presented promising results in advancing novel materials like LDPE to support circular economy in industrial wastewater treatment. Other Information Published in: Journal of Environmental Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jece.2024.114067